2001
DOI: 10.1007/s002040100251
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinedione toxicity to isolated hepatocytes revealed by coherent multiprobe fluorescence microscopy and correlated with multiparameter flow cytometry of peripheral leukocytes

Abstract: Thiazolidinediones (TZDs) are effective for the treatment of adult-onset insulin-resistant diabetes. Unfortunately, TZDs are associated with sporadic hepatic dysfunction that is not predictable from experimental animal studies. We investigated the response of isolated rat and human hepatocytes to various TZDs using biochemical assays, coherent multiprobe fluorescence microscopy and flow cytometric analyses. The results identified direct effects of TZD on mitochondria from live human and rodent hepatocytes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 28 publications
1
42
0
Order By: Relevance
“…36 Since then, numerous studies have identified the crucial role of ROS in causing cellular damage, [36][37][38][39] authorizing the technique as the valid and reliable substitute for other biochemical methods to detect cellular ROS. Flow cytometric detection of ROS applied in both the previous toxicologic study on hepatocytes 31 and the present study has been shown to be efficient to reveal the functional influences of potential toxicants, such as troglitazone, which have hitherto been not detected by con- ventional premarketing screening, including any animal experiments. 40,41 In this study, the OUMS-29 cells showed a gradual, but significant, decrease in unit ⌬⌿ m after long exposure to troglitazone, although not resulting in clear cell death.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…36 Since then, numerous studies have identified the crucial role of ROS in causing cellular damage, [36][37][38][39] authorizing the technique as the valid and reliable substitute for other biochemical methods to detect cellular ROS. Flow cytometric detection of ROS applied in both the previous toxicologic study on hepatocytes 31 and the present study has been shown to be efficient to reveal the functional influences of potential toxicants, such as troglitazone, which have hitherto been not detected by con- ventional premarketing screening, including any animal experiments. 40,41 In this study, the OUMS-29 cells showed a gradual, but significant, decrease in unit ⌬⌿ m after long exposure to troglitazone, although not resulting in clear cell death.…”
Section: Discussionmentioning
confidence: 71%
“…40,41 In this study, the OUMS-29 cells showed a gradual, but significant, decrease in unit ⌬⌿ m after long exposure to troglitazone, although not resulting in clear cell death. Lack of obvious cell death in troglitazone-treated hepatocytes has also been reported, 31 suggesting that the troglitazone-induced ⌬⌿ m attenuation was not a critical inducer, but a possible priming, for hepatocyte death. It was speculated that enhanced accumulation in troglitazone in the liver of poor metabolizers might attenuate ⌬⌿ m in hepatocytes, triggering subsequent events for severe hepatic damage, although candidate genetic mutations in the metabolic enzymes in the poor metabolizers, such as CYP2C8, CYP3A4, and CYP2C19, have not yet been determined.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…While normal hepatocytes tolerated troglitazone concentrations up to 100 µM without detectable mitochondrial effects, hepatocytes from one diabetic donor exhibited decreases in the mitochondrial membrane potential upon exposure to 50 µM and higher (in a second diabetic donor this was not observed) (Haskins et al, 2001). Whether liver cells from humans with T2D indeed react differently to potentially toxic drugs remains to be determined.…”
Section: Models Of T2d and Obesitymentioning
confidence: 97%
“…Thus, such responses as alteration of bioenergetics, metabolism and mitochondrial function are PPARγ-independent [17]. The order of toxicity by which TZDs cause mitochondrial dysfunction is troglitazone>pioglitazone and rosiglitazone [14,43]. The hierarchy of clinical and cellular hepatotoxicity correlates strongly to mitochondrial impairment and not to PPARγ affinity [14,17,43].…”
Section: Reactive Metabolite/reactive Oxygen Species (Ros)mentioning
confidence: 99%